At the Hawk’s Well A Theoretical and Practical Study about the Music in the Play - Amalfi, Maestro Marcello (ABEI Journal, 2015)
William Butler Yeats (1865-1939) is a pillar of the so-called Irish Literary Revival. His work has influenced authors such as T. S. Eliot (1888-1965) and Samuel Beckett (1906-1989), among many others. He is best knownfor his poetry than for his dramaturgical texts, and above all, for havingbeen awarded a literature Nobel Prize in 1923. Nonetheless, his work for the theatre has a great value, and it is now being rediscovered by artists from all around the world.The aim of this article is to visit part of that production, in order to write about and record the original music for the opening of At the Hawk’s Well (1916). To achieve this goal, a theoretical research has been held covering texts and studies about the author, the play and its stage production; it was followed by a practical investigation that includes a search for rhythms, sounds, timbres and characteristic instruments, as well as the appropriate way to execute and record them in studio.